Predictors of membership in music therapy professional organizations - Bevilacqua, Lauren F., author; Knight, Andrew, advisor; LaGasse, Blythe, committee member; Lopes, Tobin, committee member (Colorado State University. Libraries, 2019)
A healthy professional membership organization is vital to the longevity and sustainability of a profession. The purpose of this survey study is to identify predictive variables that determine if a professional music therapist becomes a member, former member, or never a member of the professional membership organization. Within the context of social exchange theory and social identity theory, it was hypothesized that a strong sense of cost-to-benefit exchange and professional identity are predictors of professional membership. The Predictors of Membership in Music Therapy Organizations questionnaire consisted of satisfaction questions and the Professional Identity and Organizational Identity scales (Mael & Ashforth, 1992). Out of 7590 board certified music therapists, 948 responded (570 were current American Music Therapy Association (AMTA) members, 335 were former members and 43 had never been members). Members were more likely to recommend membership. Most music therapists who are former members or have never been members indicated that they would join the organization if financial assistance was available. Music therapists scored higher on the professional identity scale than on the organizational scale. There was no statistical significance between professional and organizational identity scores between those who were unlikely to recommend AMTA membership and those who were neutral or moderately unlikely to recommend membership. Results support the ideas of social exchange and professional identity with organizational identity predicting satisfaction ratings with AMTA. Considerations for future research and practical application of the data are discussed.
Keywords: music therapy; membership; profession